2022
DOI: 10.1038/s41564-022-01163-3
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibody activity against 21 SARS-CoV-2 variants in older adults vaccinated with BNT162b2

Abstract: SARS-CoV-2 variants may threaten the effectiveness of vaccines and antivirals to mitigate serious COVID-19 disease. This is of most concern in clinically vulnerable groups such as older adults. We analysed 72 sera samples from 37 individuals, aged 70–89 years, vaccinated with two doses of BNT162b2 (Pfizer–BioNTech) 3 weeks apart, for neutralizing antibody responses to wildtype SARS-CoV-2. Between 3 and 20 weeks after the second vaccine dose, neutralizing antibody titres fell 4.9-fold to a median titre of 21.3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 44 publications
6
39
0
1
Order By: Relevance
“…We observed marginally lower neutralizing antibodies and cellular immune responses among adults aged ≥80 years compared with adults aged 65-79 years. This is consistent with previous studies of BNT162b2 that found lower neutralizing antibody responses in older adults compared with younger adults [16,17]. This underscores the importance of choice of vaccine in older adults.…”
Section: Discussionsupporting
confidence: 92%
“…We observed marginally lower neutralizing antibodies and cellular immune responses among adults aged ≥80 years compared with adults aged 65-79 years. This is consistent with previous studies of BNT162b2 that found lower neutralizing antibody responses in older adults compared with younger adults [16,17]. This underscores the importance of choice of vaccine in older adults.…”
Section: Discussionsupporting
confidence: 92%
“…There are a variety of neutralization assays that have been described to be able to measure functional antibody neutralization against wild-type as well as variant SARS-CoV-2 that involve binding proxy assays ( 24 27 ), pseudovirus, or VLP neutralization ( 7 , 25 , 26 ) as well as SARS-CoV-2 culture-based neutralization ( 26 , 28 ). Not all methods compare wild-type or variant SARS-CoV-2 neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…The beta variant was the most neutralization- and vaccine-resistant of the first four variants of concern, including the delta strain [ 45 ]. In contrast, Newman et al observed no neutralizing capacity against the beta variant of SARS-CoV-2 in sera of elderly people vaccinated twice with BT [ 46 ]. The differences in neutralization potential of α-Spike-Ab between the studies might be explained on the one hand by the presence of younger participants in our study, and on the other, by a third inoculation with the mRNA vaccine after six months.…”
Section: Discussionmentioning
confidence: 99%